2018
DOI: 10.1017/s002531541800108x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling estuarine copepods at different scales and resolutions: a study in Rio de la Plata

Abstract: In the Rio de la Plata salinity, temperature, chlorophyll a (chl a), and densities (ind. m−3) of the copepods Acartia tonsa and Paracalanus parvus were measured from January to November in 2003 by following a nested weekly and monthly design. Such sampling yielded two separate datasets: (i) Yearly Dataset (YD) which consists of data of one sampling effort per month for 11 consecutive months, and (ii) Seasonal Weekly Datasets (SWD) which consists of data of one sampling effort per week of any four consecutive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…al., 1991;Bhattacharya et al, 2014a). Paracalanus parvus, which is generally found in coastal, neritic and brackish waters, is a warm-water herbivorous copepod that generally feeds on diatoms (Checkley, 1980;Paul and Calliari, 2019). A study of hourly changes of the copepod community of the Muriganga revealed that P. parvus has an overlapping niche with B. similis when the Muriganga remains ecologically stable; however, after any cyclonic disruption P. parvus is replaced by A. tortaniformis Paul et al, 2020b).…”
Section: Copepod Community Of Murigangamentioning
confidence: 99%
See 1 more Smart Citation
“…al., 1991;Bhattacharya et al, 2014a). Paracalanus parvus, which is generally found in coastal, neritic and brackish waters, is a warm-water herbivorous copepod that generally feeds on diatoms (Checkley, 1980;Paul and Calliari, 2019). A study of hourly changes of the copepod community of the Muriganga revealed that P. parvus has an overlapping niche with B. similis when the Muriganga remains ecologically stable; however, after any cyclonic disruption P. parvus is replaced by A. tortaniformis Paul et al, 2020b).…”
Section: Copepod Community Of Murigangamentioning
confidence: 99%
“…Estuarine ecological studies have traditionally focused on the patchy distribution of copepods, presence/absence of certain species, values of various diversity indices, and their relationships with environmental gradients, to draw inferences on the ecological stress of estuaries (Lawrence et al, 2004;Rice et al, 2015;Paul et al, 2016;Paul and Calliari, 2019). Changes of diversity, abundance and distribution of copepods are, therefore, considered as indicators of ecological stresses of estuaries that arise from abiotic, seasonal, climate changes and human-interventions (Sinha et al,1996;Hoof and Peterson, 2006;Sullivan et al, 2007;Lin et al, 2011;Paul et al, 2016;Araujo et al, 2017).…”
Section: Copepod Community As Indicator Of Ecological Stress Of Estuariesmentioning
confidence: 99%